Digital Learning Resources in Islamic Religious Education: A Literature Review (Journal Of Islamic Education And Pesantren, 2025)
This study aims to comprehensively describe the types and formats of digital learning resources relevant to Islamic Religious Education (IRE) through a literature-based review. The research adopts a descriptive qualitative approach using a literature study of various scholarly sources published between 2010 and 2024. Data were analyzed through content analysis and thematic analysis to identify the characteristics, classifications, and potential uses of digital learning resources in the context of IRE instruction. The findings indicate that digital learning resources in IRE encompass seven main types, namely e-books, instructional videos, podcasts, online learning platforms, interactive simulations, educational games, and collaborative forums. These resources are available in various digital formats, such as PDF, ePub, MP4, MP3, HTML, and SCORM, and can be accessed through a range of digital devices, including computers, tablets, and smartphones. The results suggest that the use of digital learning resources has the potential to enhance the accessibility, flexibility, and effectiveness of IRE learning. However, their optimal utilization requires adequate digital infrastructure, improved digital competencies of educators and learners, and the development of high-quality, contextualized IRE content. This review is expected to serve as a conceptual reference for educators and instructional developers in integrating digital learning resources more systematically and adaptively into Islamic Religious Education.